Determination of complications in computed tomography guided fine needle aspiration cytology of lung mass - Joshi, BR; Khadgi, K; Ghimire, RK (Journal of Institute of Medicine Nepal, 2016)
Introduction: The purpose of this study was to determine the complications of computed tomography (CT) guided fine needle aspiration cytology (FNAC) of lung mass. Methods: This prospective study was done in 56 patients in Department of Radiology and Imaging, Tribhuvan University Teaching Hospital (TUTH). The CT guided FNAC was performed in patients having lung mass. The complications during CT guided FNAC were recorded and statistical analysis was done. Results: Among 56 individuals 29 were males and 27 were females, age ranging from 42 to 80 years. Most of the lesions were located in upper lobe of lungs. There were no complications in 34 cases whereas 16 cases had local hemorrhage, 5 cases had pneumothorax of less than 30% and 1 case had pneumothorax of more than 30%. Conclusion: CT guided FNAC is a safe procedure for diagnostic accuracy without significant complications.